The use of social and psychological factors in the practice of team management in crisis conditions - Qiao Baoshu (Kharkiv : V. N. Karazin Kharkiv national university, 2024)
The object of the study is social and psychological methods in the enterprise management. The subject of the study is the practice of ensuring the use of psychosocial factors in team management under crisis conditions. The purpose of this master's thesis is to provide a theoretical demonstration of the basis of the socio-psychological factors of business management, to reveal the current practice and development prospects of business personnel management organizations, and to find directions for the improvement of this work on the basis of systemizing other new suggestions on this issue. On the basis of the research results, this paper puts forward some theoretical and practical suggestions on the improvement of the personnel management system of Jingdong Enterprise. The obtained results can be used to develop a methodological basis for designing personnel management mechanisms in enterprises as a means of preventing their internal threats. their internal threats.
Scientific advisor: Shevchenko V., PhD in philology, associate professor, department management, business and professional communications
Keywords: SOCIAL SCIENCES::Social sciences; management; personnel; personnel management; labor resources; socio-psychological methods; motivation; efficiency of personnel management